Assistance with Basic English Learning for Students on Islamic Boarding School As'adiyah Sengkang - Razak, Yusuf; Munawir, Ahmad; Latif, Fatmawati; Abdullah, S Muh Raja; Fitriyyah, Meiliana (Education and Talent Development Center of Indonesia, 2022)
The female dormitory students of the As'adiyah Sengkang Islamic Boarding School who are also students at Madrasah Tsanawiyah and Madrasah Aliyah were the objectives of this program, which began at the start of the 2020/2021 academic year. This activity is being carried out to provide students with an understanding of the English language. Learning in Islamic boarding schools has never previously provided intensive English learning so that students not only gain religious knowledge but also gain English knowledge that will be useful after they graduate. For four and a half months, this activity was carried out by delivering basic English elements such as grammar, vocabulary, and conversation. Students enjoyed this activity. This demonstrates their desire to improve their English skills.